Importance of family history of colorectal carcinoma in situ versus invasive colorectal cancer: a nationwide cohort study - Tian, Yu; Kharazmi, Elham; Brenner, Hermann; Xu, Xing; Sundquist, Kristina; Sundquist, Jan; Fallah, Mahdi (Journal of the National Comprehensive Cancer Network, 2021)
Background: The aim of this study was to explore the risk of invasive colorectal cancer (CRC) in relatives of patients with colorectal carcinoma in situ (CCIS), which is lacking in the literature. Patients and Methods: We collected data from Swedish family-cancer datasets and calculated standardized incidence ratio (SIR) and cumulative risk of CRC in family histories of CCIS in first- and second-degree relatives. Family history was defined as a dynamic (time-dependent) variable allowing for changes during the follow-up period from 1958 to 2015. Of 12,829,251 individuals with available genealogical data, 173,796 were diagnosed with CRC and 40,558 with CCIS. Results: The lifetime (0-79 years) cumulative risk of CRC in first-degree relatives of patients with CCIS was 6.5%, which represents a 1.6-fold (95% CI, 1.5-1.7; n=752) increased risk. A similarly increased lifetime cumulative risk (6.7%) was found among first-degree relatives of patients with CRC (SIR, 1.6; 95% CI, 1.6-1.7; n=6,965). An increased risk of CRC was also found in half-siblings of patients with CCIS (SIR, 1.9; 95% CI, 1.1-3.0; n=18) and also in half-siblings of patients with CRC (SIR, 1.7; 95% CI, 1.3-2.1; n=78). Moreover, the increased risk of CRC was higher for younger age at diagnosis of CCIS in the affected first-degree relative and for younger age at diagnosis of CRC in the index person. Conclusions: Results of this study show that first-degree relatives and half-siblings of patients with CCIS have an increased risk of CRC, which is comparable in magnitude to the risk of those with a family history of invasive CRC. These findings extend available evidence on familial risk of CRC and may help to refine guidelines and recommendations for CRC screening.
Gesehen am 19.01.2022